Loss of Livelihood, Wages, and Employment During the COVID-19 Pandemic in Selected Districts of Chhattisgarh in India, and Its Impact on Food Insecurity and Hunger - Jeyakumar, Angeline; Dunna, Devishree; Aneesh, Mitravinda (Frontiers in Public Health, 2022)
Food security assessments in different geographical settings during the COVID -19 pandemic in India are few, yet vital to ascertain interventions and for emergency preparedness. We selected an Empowered Action Group state, Chattisgarh in India to assess availability, accessibility, and affordability during the first wave of the pandemic using the FAO, HFIAS questionnaire, in a random sample (N=401) from two districts. Total food security scores were derived by summing the individual scores for food security variables. Percentages above and below the median scores were used to assess food insecurity. Proportion Z test was used to compare settings and a generalized linear model was used to determine the association between dependent and independent variables. Almost 63% represented the non-tribal regions. Results identified a greater percentage of non-tribal participants (77%) scored ≤ median (8) representing high food insecurity and 88.5% of tribal respondents scored above the median (9) indicating better food security. Among the determinants, settings, family income, and income loss were significantly associated with accessibility and affordability scores, whereas settings and income loss were associated with the availability and hunger scores. In the non-tribal settings, young age (< 45 years), and being female, and income loss increased the odds of food insecurity. While India is expecting the next wave, actions urgent and targeted towards the vulnerable sections in the population should be prioritized to endure and overcome the impact of the pandemic.